2018
DOI: 10.1002/jum.14727
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Prolotherapy for Acromial Enthesopathy and Acromioclavicular Joint Arthropathy: A Single‐Arm Prospective Study

Abstract: Ultrasound-guided prolotherapy with a 15% dextrose solution is an effective and safe therapeutic option for moderate-to-severe acromial enthesopathy and acromioclavicular joint arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…While they are frequently used to help get athletes through the season, they should not be used in lieu of activity modifications or rehabilitation programs given the risk of continued osteolysis and disease progression (20). Other injection options, such as prolotherapy or autologous adipose-derived mesenchymal stem cell therapy, have been described in the treatment of ACJ pathology, but there are currently no studies supporting their use in isolated DCO (44,45).…”
Section: Role Of Acj Injectionsmentioning
confidence: 99%
“…While they are frequently used to help get athletes through the season, they should not be used in lieu of activity modifications or rehabilitation programs given the risk of continued osteolysis and disease progression (20). Other injection options, such as prolotherapy or autologous adipose-derived mesenchymal stem cell therapy, have been described in the treatment of ACJ pathology, but there are currently no studies supporting their use in isolated DCO (44,45).…”
Section: Role Of Acj Injectionsmentioning
confidence: 99%
“…All of studies reported about good improvement of pain using the VAS score after dextrose prolotherapy treatment. A total of 6 studies reported improvement in supraspinatus tendon tear or pathology [8][9][10][11][12][13], 6 studies reported in Achilles tendon cases [4,[14][15][16][17][18] studies reported improvement in pain VAS score in treatment of patellar tendon, meniscus, acromion enthesopathy, anterior cruciate ligament laxity and anterior tibiofibular ligament injury [19][20][21][22][23].…”
Section: Pain Visual Analog Scale Scorementioning
confidence: 99%
“…There are nine studies (52%) used the concentration of dextrose with 25% [8,9,12,14,16,17,22,23,28] while three studies each used concentrations with 20% [11,15,18] or 15% [19][20][21]. The other two studies used concentrations of 10% [23] and 16.5% [13].…”
Section: Concentration Of Dextrose and Injection Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Smaller studies have given some plausible insight for the use of prolotherapy for the ACJ and complex shoulder injuries, however, there are no larger trials to reinforce these findings. 30,31 Rehabilitation following orthobiologic therapy is described by the American Physical Therapy Association as the integration of interventional orthobiologic techniques coupled with appropriate rehabilitation strategies that harness the healing mechanisms through movements to augment the orthobiologic therapies. 12 The goal of rehabilitation after orthobiologic therapy is to return a patient to optimal function by combining the science and research behind both rehabilitation and regenerative medicine.…”
Section: Introductionmentioning
confidence: 99%